Endophytic Bacterium Pseudomonas fluorescens RG11 May Transform Tryptophan to Melatonin and Promote Endogenous Melatonin Levels in the Roots of Four Grape Cultivars - Ma, Yaner; Jiao, Jian; Fan, Xiucai; Sun, Haisheng; Zhang, Ying; Jiang, Jianfu; Liu, Chonghuai (Frontiers in Plant Science, 2017)
Endophytes have been verified to synthesize melatonin in vitro and promote the abiotic stress-induced production of endogenous melatonin in grape (Vitis vinifera L.) roots. This study aimed to further characterize the biotransformation of tryptophan to melatonin in the endophytic bacterium Pseudomonas fluorescens RG11 and investigate its capacity for enhancing the endogenous melatonin levels in the roots of different grape cultivars. Using ultra performance liquid chromatography-tandem mass spectrometry combined with 15N double-labeled L-tryptophan as the precursor for melatonin, we detected isotope-labeled 5-hydroxytryptophan, serotonin, N-acetylserotonin, and melatonin, but not tryptamine during the incubation of P. fluorescens RG11 in vitro; the production capacity of these four compounds peaked at the exponential growth phase. RG11 colonization increased the endogenous levels of 5-hydroxytryptophan, N-acetylserotonin, and melatonin, but reduced those of tryptamine and serotonin, in the roots of the Red Globe grape cultivar under salt stress conditions. Quantitative real-time PCR revealed that RG11 reduced the transcription of the grapevine tryptophan decaboxylase and serotonin N-acetyltransferase genes when compared to the un-inoculated control; these results were correlated with the decreased reactive oxygen species (ROS) burst and cell damage alleviated by RG11 colonization under salt stress conditions. Additionally, RG11 promoted plant growth and enhanced the levels of endogenous melatonin in different grape cultivars. Intraspecific variation in the levels of melatonin precursors was found among four grape cultivars, and their root crude extracts appeared to significantly induce the melatonin biosynthesis of RG11 in vitro. Overall, this study provided useful information to better understand the potential melatonin synthesis pathway in rhizobacteria and revealed plant-rhizobacterium interactions that affect melatonin biosynthesis of plants under abiotic stress conditions.